2020
DOI: 10.1007/s40944-020-00421-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Gynecological Oncology Care: Glimpse into Association of Gynecological Oncologists of India (AGOI) Perspective

Abstract: Purpose The notorious COVID 19 pandemic has caused rapid and drastic changes in cancer care worldwide in 2020. This online survey aims to assess the extent to which the pandemic has affected cancer care in gynecological oncology amongst members of the Association of Gynecological Oncologists of India (AGOI), a registered professional society founded in 1991. Methods We developed and administered a cross-sectional, flash survey to members of AGOI in the first week of April 2020. Data were analyzed using Microso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Gultekin et al (2021) also reported that patients worried about their disease progression if their treatment or follow-up was delayed (Gultekin et al 2021). An article stated that restrictions/lockdowns disrupt patient access to health facilities, which causes delays in treatment (Bhandoria et al 2020). In this study, 61.7% of patients stated that there was no effect of government restrictions on accessing and delaying their treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Gultekin et al (2021) also reported that patients worried about their disease progression if their treatment or follow-up was delayed (Gultekin et al 2021). An article stated that restrictions/lockdowns disrupt patient access to health facilities, which causes delays in treatment (Bhandoria et al 2020). In this study, 61.7% of patients stated that there was no effect of government restrictions on accessing and delaying their treatment.…”
Section: Discussionmentioning
confidence: 64%
“…This needs to be discussed with the patient, before, making any decision. 12 For follow-up of gynecological malignancy cases, oncologists and their patients need to discuss the necessity of avoiding clinic visits, due to higher risk of morbidity and mortality from COVID-19 and choose telemedicine facility instead if applicable. Another issue of significance is the tough decision for both patients and oncologists to continue immuno-suppressive treatments during this COVID-19 crisis.…”
Section: Gynecological Cancer Burden In Indiamentioning
confidence: 99%
“…In an online survey conducted amongst gynecologists, gynecologic oncologists, surgical oncologists, radiation oncologists, and medical oncologists of Association of Gynecological Oncologists of India (AGOI), 54% respondents felt that alternative learning methods like virtual conferences, online reading material through professional society websites, and limited gathering were necessary to inform medical practices, but expressed concern that there would be few opportunities for professional interaction and networking. 12…”
Section: Introductionmentioning
confidence: 99%
“…Early in the pandemic, in June 2020, an online survey of the Association of Gynecologic Oncologists of India was distributed to assess the response to changes in gynecologic cancer treatment. At that time, cervical cancer was managed with standard optimal therapy (surgery or definitive chemoradiation, depending on stage) for two-thirds of patients whereas in about a third of patients, neoadjuvant chemotherapy was used to delay surgery, a proven alternative in a limited resource setting 15…”
Section: Real World Accountsmentioning
confidence: 99%
“…At that time, cervical cancer was managed with standard optimal therapy (surgery or definitive chemoradiation, depending on stage) for twothirds of patients whereas in about a third of patients, neoadjuvant chemotherapy was used to delay surgery, a proven alternative in a limited resource setting. 15 At Tata Memorial Hospital in Mumbai, Indian, physicians documented their procedural changes for gynecologic cancer during the lockdown period between March 23 and June 30, 2020. These included: suspension of all concurrent chemotherapy for cervical, endometrial, and vulvo-vaginal cancers during radiation, given that most of their patient populations were from geographic locations with high rates of COVID-19; preferential use of hypofractionated external beam treatment for elderly patients (age >75 years) to minimize the need for travel; and preferential use of single application with multiple fractions of intracavitary interstitial brachytherapy or multiple applications with reduced time interval to prevent inpatient admissions and procedures.…”
Section: Real World Accounts Asia Pacificmentioning
confidence: 99%